Social Support And Client Satisfacation With Visual Inspection Acetate Acid (Via) - Reca Dwi Putri Suswanti; Gatut Hardianto; Samsriyaningsih Handayani (Journal of Midwifery, 2021)
Introduction: This study was conducted to show that early prevention and treatment of cervical cancer can save on treatment costs. Cervical cancer is one of the biggest threats to women's health. This is related to the low awareness of women who have had active sexual relations in carrying out early detection of cervical cancer so that it can increase the incidence of cervical cancer. The purpose of this study was to determine the relationship between social support and client satisfaction on IVA service satisfaction by public health center officers. Methods: This study used an observational analytic study with a retrospective cohort design. The sample size used was 70 respondents with the same distribution in each control group and the exposed group, each using 35 respondents. The sampling technique used consecutive sampling. Univariate analysis using Chi-Square test. Bivariate analysis using Spearman correlation test. Results: The results of Univariate analysis in the control group and the exposed group showed that age (p= 0.4), education (p= 0.136), occupation (p= 0.622), length of marriage (p= 0.073), number of sexual partners (p= 0.073). = 0.602) and the number of children (p = 0.151). The results of bivariate analysis showed that husband's support (p= 0.735), mother's support (p= 0.984), health cadre support (p= 0.320) and peer support (p= 0.725). There is no relationship/correlation between social support and service satisfaction. Conclusion: There are other factors that can affect the satisfaction of women of childbearing age with early detection of cervical cancer (VIA) apart from social support.